Jiangtang Tongmai Prescription Reduced Diabetic Lung Injury Through SnoN and TGF-β1/Smads Signaling Pathway - Ding, Nian; Zheng, Chenghong (Frontiers in Endocrinology, 2022)
Abstract: To establish diabetes model in rat and intervene with Jiangtang Tongmai Prescription (JTTMP) to explore the repairing effect of JTTMP on diabetic lung injury. The type II diabetes model was used to establish the rat diabetes model by streptozotocin (STZ) induction. Different doses of JTTMP and metformin were used to intervene, the blood was collected to detect the blood glucose of each group of rats; HE (Hematoxylin) staining was to detect the morphological changes of rat lung tissue; ELISA was to detect the expression of IL-6, TNF-a, IL-1β in serum and lung tissue of each group of rats; The level of TGF-β1, SnoN, Smad2, Smad3, Smad7 and other signaling pathway proteins were tested by Western blot. In comparison with the normal control (NC) group, rats in the diabetes model (DM) group lost weight and increased blood sugar significantly, the level of TGF-β1, Smad2/3 were rised in DM group but Smad7 was decreased; while after 8 weeks of JTTMP intervention, the level of TGF-β1 and Smad2/3 decreased but Smad7 increased; blood sugar decreased significantly and the expression of inflammatory factors in lung tissue decreased. JTTMP may activate SnoN and the downstream TGF-β1/Smads signaling pathway to repair diabetic lung injury, which will have important application prospects in the clinical treatment of diabetes against lung injury in the future. Key words JTTMP;TGF-β1/Smads signal; SnoN protein; diabetic lung injury